Pengalaman Psikologis Korban Penculikan Masyarakat Moro Di Tobelo - Dince Deti Fenina; Arthur Huwae (Fakultas Psikologi Universitas Wisnuwardhana Malang, 2022)
Moro is one of the kingdoms in North Maluku whose where abouts have been unknown since the 16th century. There is a belief from the Tobelo community that the Moro are still together but not seen. Several cases of the disappearance of the Tobelo people are believed to be kidnapping by the Moro people because they disappear unreasonably and often speak for themselves after the kidnapping case. The purpose of this study is to describe what Tobelo residents have experienced who have been abducted by the Moro people and identify the psychological impact of being kidnapped by the Moro people. This study uses a qualitative method with a phenomenological approach. Data was collected by interviewing and observing 2 participants who were Tobelo people and had been abducted by the Moro people. The findings of this study indicate the occurrence of trance in the participants, which is believed to be the action of the Moro community, the existence of unconsciousness when the participants were kidnapped by the Moro, and the participants believed in the existence of the Moro world because they had been in that place. However, the psychological condition of the participants also played an important role in releasing the Moro influence. Anxiety about the stigma of society is the cause of breaking up with Moro and good communication and support from parents encourage them to keep in touch with Moro. The occurrence of this kidnapping case changed the participants' view of Moro for the better because Moro was considered to be a friend of the participants.